Comparison of "plain conditions" and "close-to-reality conditions" for evaluation of biomechanical load spectra of handball shoes - Krumm, D.; Gläser, A.; Schlegel, G.; Odenwald, S. (Procedia Engineering, 2016)
The purpose of this paper was to compare two different testing conditions during the acquisition of biomechanical load spectra for handball shoes. Subjects performed two typical handball activities, i.e. feints and jump shots, either under "plain conditions" (group I) or "close-to-reality conditions" (group II). While subjects of group II performed their tasks with a handball and an obstacle in front of them that simulated a defense player, subjects of group I performed their tasks without any additional items. In total, 19 experienced amateur handball players provided written informed consent and participated. Kinematics and kinetics were recorded using an optoelectronic measurement system and a force plate. Biomechanical load spectra, which can be used to synthesize mechanical simulations for characterization of handball shoes, were evaluated from normalized vertical ground reaction forces, forefoot bending angles and temporal spatial parameters. Statistical tests such as one-way analysis of variance were conducted to test for significant differences between both groups. The results showed that the mean of maximum vertical ground reaction forces between both groups was significantly different for feints (2.2 body weight vs. 2.5 body weight) and jump shots (2.7 body weight vs. 3.1 body weight) with higher values for group II. The maximum bending angles during feints were not significantly different (17.6° vs. 17.2°), whereas the angles during jump shots were significantly different between both conditions (32.2° vs. 22.2°). In conclusion, subjects of group II showed higher effort in performing their tasks compared to subjects of group I. Therefore, the authors suggest that the acquisition of biomechanical load spectra should be performed under real conditions or at least "close-to-reality conditions".